Faktor Penyebab Abortus di Indonesia Tahun 2010-2019: Studi Meta Analisis - Akbar, Aidil (Jurnal Biomedik : JBM, 2019)
Abstract: Abortion is often associated with bleeding and death in pregnancy. The incidence of abortion in Indonesia reaches 2.3 million annually. This meta-analysis study was aimed to determine the causal factors of abortion in Indonesia from 2010 to 2019. This meta-analysis study was conducted by collecting articles in official national scientific journals through the Google Scholar application relating to the causal factord of abortion in most provinces in Indonesia from 2010 to 2019. The results showed that there were 43 articles collected from 22 provinces in Indonesia, which involved 5707 total samples. Data analysis showed that there were eight main causes of abortion in Indonesia from 2010 to 2019, namely: maternal age during pregnancy (27 conclusions), parity (21 conclusions), history of abortion (10 conclusions), interparity interval (9 conclusions), gestational age (7 conclusions), level of education (6 conclusions), employment (6 conclusions), and anemia (5 conclusions). In conclusion, maternal age and parity are the leading factors of abortus in Indonesia. It is expected that the eight main causes of abortion could be the basis for health workers in making decisions in community education, therefore, the incidence of abortion and maternal mortality can be reduced.Keywords: abortion causal factorÂ Abstrak: Abortus sering dikaitkan dengan kasus perdarahan dan kematian pada ibu hamil. Angka kejadian abortus di Indonesia mencapai 2,3 juta setiap tahunnya. Studi meta analisis ini bertujuan untuk mengetahui faktor penyebab abortus di Indonesia dari tahun 2010 hingga tahun 2019. Studi ini dilakukan dengan mengumpulkan artikel pada jurnal ilmiah nasional resmi melalui aplikasi google scholar yang berkaitan dengan faktor kejadian abortus di sebagian besar provinsi di Indonesia mulai tahun 2010 hingga tahun 2019. Hasil penelitian mendapatkan 43 artikel yang berasal dari 22 provinsi di Indonesia dan melibatkan 5707 total sampel. Hasil analisis mendapatkan delapan faktor penyebab tertinggi abortus di Indonesia dari tahun 2010 hingga 2019 yaitu: umur ibu saat hamil (27 simpulan), paritas (21 simpulan), riwayat abortus (10 simpulan), jarak kehamilan (9 simpulan), usia kehamilan (7 simpulan), tingkat pendidikan dan pekerjaan (masing-masing 6 simpulan), serta anemia (5 simpulan). Simpulan penelitian ini ialah usia dan paritas merupakan faktor penyebab abortus yang utama di Indomesia. Dengan diketahui delapan faktor penyebab tertinggi abortus ini diharapkan dapat menjadi dasar bagi tenaga kesehatan dalam mengambil keputusan dalam hal edukasi kepada masyarakat sehingga diharapkan angka kejadian abortus dan kematian ibu hamil dapat diturunkan.Kata kunci: faktor penyebab abortus